THE EFFECT OF PjBL-STEM LEARNING MODEL ON STUDENTS’ COGNITIVE SKILL IN MATTER SUBSTANCES AND THEIR CHANGES SUBJECT - Mufidah G; Rahmah Evita Putri; Rani Oktavia; Firda Azzahra (UNIVERSITAS NEGERI MEDAN, 2024)
The background of this research was the results of the researcher's observations on 8th grade students of SMPN 14 Padang. Based on the results of observations, information was obtained that teachers had previously implemented the PjBL learning model but never had implemented the STEM approach, and teachers had never combined the learning model with the STEM approach. The purpose this research was to examine the effect of the PjBL-STEM learning model on students' cognitive skill regarding substances and their changes subject. The type of research used was Quasi Experimental, design, using a Posttest Control Group Design. This research used two classes, there were experimental and the control class. The experimental class uses the PjBL-STEM learning model, while the control class used a conventional approach learning model. Sampling in this study was carried out using a purposive sampling technique, based on almost the similliary average daily test scores. The instrument of this research were multiple choice test with 20 questions. The results of data analysis show that the cognitive skill of students in the experimental class are higher than those in the control class. The used of the PjBL-STEM learning model makes a good difference in students' cognitive abilities. The results of hypothesis testing based on posttest data obtained from the two sample classes showed that, H0 was rejected and H1 was accepted, so it can be interpreted that there is a difference in the average cognitive abilities of students in the experimental class and the control class. There is an effect of the application of the PjBL-STEM learning model on the students’ cognitive skill on substance material and its changes subject.